The Postponement of the Implementation of Inheritance Distribution in The Seunuddon Community, North Aceh In The Lens Of ‘Urf Theory and Legal Pluralism - Abubakar, Ali; Achyar, Gamal; Khatimah, Husnul; A. Samad, Sri Astuti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The objective of this study is to investigate the act of postponing the execution of inheritance distribution in the Seunuddon village, located in North Aceh. This study employs sociological legal approaches, which are examined through the lenses of al-'urf and the notion of legal pluralism. Data was gathered through extensive interviews conducted with religious leaders, community leaders, and successors. This study determined that delays in the distribution of inheritance in Seunuddon had persisted for an extended period, with some cases resulting in patah titi and subsequent complications. The delay arises due to entrenched customs, the survival of one parent, inadequate economic conditions, lack of family discussions regarding inheritance division, reluctance to distribute the inheritance immediately due to feelings of embarrassment, and the incapacity of young children to handle the inheritance. Secondly, while examining customary Islamic law, the act of delaying the allocation of inheritance is encompassed within the concepts of 'urf sahih (valid custom) and 'urf fasid (invalid custom). Out of the four cases examined, three cases did not present any issues related to inheritance, as each party got and obtained the legacy funds. Nevertheless, there are instances in which the designated successor has deceased (patah titi), leading to complications in the process of inheriting assets. Within the framework of 'urf theory, the initial three instances can be classified as 'urf sahih, however, the final instance is deemed 'urf fasid due to its propensity for generating injustice, albeit preserving the bond of brotherhood. According to the doctrine of legal pluralism, there exists a dialectic and accommodation between Islamic law and societal customs to provide social harmonization and integration.